2021
DOI: 10.31234/osf.io/qd75k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring memory is harder than you think: How to avoid problematic measurement practices in memory research

Abstract: There is a crisis of measurement in memory research, with major implications for theory and practice. This crisis arises because of a critical complication present when measuring memory using the recognition memory task that dominates the study of working memory and long-term memory (“did you see this item? yes/no” or “did this item change? yes/no”). Such tasks give two measures of performance, the “hit rate” (how often you say you previously saw an item you actually did previously see) and the “false alarm ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 143 publications
(187 reference statements)
1
14
0
Order By: Relevance
“…We found that the continuous resource model was essentially unrecoverable across the three studies when BIC was used to compare models (Figure 3B). The particular instantiation of the resource model used by these authors has more parameters than the discrete-slot model, so these results with BIC align with prior work in which BIC was incorrectly biased towards models with fewer parameters (e.g., Robinson et al, 2021;van den Berg, et al, 2014). We also found that AIC failed to reliably recover the continuous resource model in the Rouder et al (2008) study and in Experiment 1 of Donkin et al (2014).…”
Section: Resultssupporting
confidence: 81%
“…We found that the continuous resource model was essentially unrecoverable across the three studies when BIC was used to compare models (Figure 3B). The particular instantiation of the resource model used by these authors has more parameters than the discrete-slot model, so these results with BIC align with prior work in which BIC was incorrectly biased towards models with fewer parameters (e.g., Robinson et al, 2021;van den Berg, et al, 2014). We also found that AIC failed to reliably recover the continuous resource model in the Rouder et al (2008) study and in Experiment 1 of Donkin et al (2014).…”
Section: Resultssupporting
confidence: 81%
“…These tasks are a variant of an “old/new” recognition memory paradigm in which participants are probed on their memory by being asked “Did you previously see this item?” or are prompted to identify an item as either “old” or “new.” In a typical visual working memory display (see Figure 1), participants see several simple, isolated objects on a solid color background and are asked to hold these items in mind before being asked to detect whether a particular object changed after a brief delay (Luck & Vogel, 1997). 1 Despite their ubiquity, change detection tasks cannot provide an unambiguous estimate of memory performance because any measure of performance from this task relies on assumptions about the distribution of memory signals which are often false and regularly unverified (see Brady et al, 2021).…”
Section: Change Detection Cannot Unambiguously Measure Memory Perform...mentioning
confidence: 99%
“…This introduces significant ambiguity into memory measurement since there are several choices for how to combine hits and false alarms into a quantitative measure of performances (e.g., d , A’, K values, percent correct, etc. ), all of which rest on different, and sometimes incompatible, theoretical and/or parametric assumptions (for a review, see Brady et al, 2021).…”
Section: Change Detection Cannot Unambiguously Measure Memory Perform...mentioning
confidence: 99%
See 1 more Smart Citation
“…These prior studies have used binary old/new memory tests, from which a single hit rate and false alarm rate are obtained for items in each condition. However, collecting multiple hit and false alarm rates per participant and encoding condition is essential to measure latent memory signals accurately because hit rates alone are susceptible to response biases that obscure the true strength of the underlying memory trace (Brady et al, 2021;Macmillan & Creelman, 1990). For example, a participant might adopt a very stringent criterion and only endorse an item as old if they are very confident and can retrieve many details.…”
Section: Introductionmentioning
confidence: 99%